(untitled) (Asian Business Research, 2016)
Based on social network theory and RBV theories, the paper adopts cross case studies research method to analyze how network relationship facilitates born global companies to acquire resources in their internationalization process through three Chinese born global company case studies. The research indicates that born global company’s network relationship built up in internationalization process can be classified into domestic strong ties, domestic weak ties, foreign strong ties and foreign weak ties in line with network ties’ strength and geographic dispersion. Those four types of network ties play very important as well as differentiated roles in Chinese born global companies’ internationalization process.